Feasibility evaluation on potential high volume of fa-based binder as early strength at ambient cured - Archanaah, N.; Noor Azline, M. N.; Nabilah, A. B.; Nor Azizi, S.; Jaafar, Mohd Saleh (Springer Science and Business Medi, 2024)
In general, strength development of fly ash-based geopolymer composite is still in focus of some researchers due to its low strength gain under ambient condition, particularly at early age of strength. An alternative way in formulating mix design for fly ash-based geopolymer with the aim to enhance the geopolymerization reactivity of fly ash in alkaline system is still in the depth of research. Many efforts have been conducted in combining various aluminosilicate materials in fly ash-based geopolymer with variation of content levels such as ground granulate blast furnace slag (GGBS), pulverzied oil palm ash (POFA), metakaolin (MK) and silica fume (SF). Despite the selection of aluminosilicate and its content level, alkaline activator concentration also gives major influence in the development of engineering properties of geopolymer composites. Therefore, it is crucial to determine the potential formulation in achieving high early strength without compromising fresh properties. Thus, this research is focusing on the evaluation of the potential binder combination of fly ash-based geopolymer paste with fly ash as the primary binder. Also, this study intended to explore the potential of POFA in enhancing the early engineering properties of fly ash-based geopolymer paste. In relation with this, the engineering properties have been evaluated which includes setting time, flowability, and compressive strength. Also, study evaluated the compatibility between the molarity and geopolymer binder combinations in achieving the promising engineering properties at the early engineering properties development. The results show that 12 NaOH concentration plays a viable role in the performance of geopolymer paste. The most pre-eminent combination is 60F40G and 60F30G10MK where both performed well in early and matured age of compressive strength. Besides that, it is also found that POFA has potential in replacement up to 30%, however combination of 60F40P with 12 M performed well at 28 days.